“They never appear on TV and if they have, I might have missed that moment.” How publics in South Africa and Germany view visible scientists - Simone Rödder; Lars Guenther; Marina Joubert (PLoS ONE, 2025)
Academic interest in scientists who regularly appear in the media dates back to Rae Goodell’s seminal book “The visible scientists”, in which she lists distinct characteristics of visible scientists, including being controversial, articulate, colorful, and reputable as a scientist. Visible scientists thus share relevant media-related characteristics that stand out in their portrayal as a group and are reminiscent of other celebrities’ characteristics. However, questions arise: what is special about the celebrity being a scientist? How many and what types of scientists fall into this category? What are the peers’ and the public’s expectations towards the social role of the visible scientist? To date, work on visible scientists has focused on theorizing them in the context of the relationship between science and its publics and empirical studies have mainly sought to characterize visible scientists and focused on single countries. This paper fills research gaps on the public perception of and expectations towards visible scientists as well as comparative studies by surveying publics in Germany and South Africa. Our data shows that Goodell’s criteria also apply to how respondents see and expect visible scientists to be. Interestingly though, a majority of non-responses to the request to name up to three visible scientists currently living in the respective country demonstrates that, overall, scientists are rather invisible to the public. Visible scientists remain a rare phenomenon despite changing media environments and a recent pandemic. In conclusion, we suggest that “visibility” (rather than “celebrity”) is the more appropriate term to refer to the temporary phenomenon of scientists who become visible in the public sphere.